2018
DOI: 10.1039/c8ob01330f
|View full text |Cite
|
Sign up to set email alerts
|

o-Nitrobenzyl photoremovable groups with fluorescence uncaging reporting properties

Abstract: o-Nitrobenzyl (o-NB) derivatives are the most widely applied photoremovable groups for the study of dynamic biological processes. By introducing different substituents to the benzylic position we were able to generate a fluorescence signal upon irradiation. This signal originates from the formation of a nitrosoketone by-product able to achieve a keto-enol tautomerism leading to pi-conjugated α-hydroxystilbene derivatives. These o-NB caging groups can be used to directly monitor the uncaging event by the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Despite this, their reactivities were found to differ by 3 orders of magnitude (Figure ). This is likely explained by the difference in the electron-donating effect between the substituents at the ortho positions of the phenyl ring, even if the substituent is three bond lengths away from the ring. , The above is further evidence for the notion that the absorption spectrum of a chromophore is not necessarily an accurate guide to its photoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, their reactivities were found to differ by 3 orders of magnitude (Figure ). This is likely explained by the difference in the electron-donating effect between the substituents at the ortho positions of the phenyl ring, even if the substituent is three bond lengths away from the ring. , The above is further evidence for the notion that the absorption spectrum of a chromophore is not necessarily an accurate guide to its photoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The first example of pro-fluorescent o-nitrobenzyl PPG was introduced in 2018 by our group. 41 One of the most commonly used PPGs for the triggering of diverse biological responses is based on the o-nitrobenzyl photochemistry. Since the photolytical release mechanism of o-nitrobenzyl PPG leads to the formation of a nitrosoketone derivative, the introduction of an aryl substituent at the benzylic position yielded to a photolysis by-product able to rearrange in a conjugated -hydroxystilbene fluorophore (by a keto-enol tautomerism).…”
Section: O-nitrobenzyl Pro-fluorescent Ppgsmentioning
confidence: 99%
“…Using this new class of o-nitrobenzyl PPGs, the photocleavage leads to an important increase of a specific fluorescence signal originating from the liberated o-nitroso by-products (Scheme 10). 41 Four different onitrobenzyl PPGs were designed and their photophysical properties were evaluated with the liberation of carboxylic acid upon irradiation at 405 nm. Interestingly, the keto-enol equilibrium is favored towards a more red-shifted fluorescent byproduct when the system is more conjugated (R= 4dimethylamino, 4-nitro and 4-methoxy phenyl) compared to a control compound (R = Br).…”
Section: O-nitrobenzyl Pro-fluorescent Ppgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies shown that 1,2-diarylethanols and their esters possess also an antimicrobial activity thus they can be used as new potential antibiotics after additional research (Kowalczyk et al 2021). The common methods for the synthesis of 1,2-diarylethanols (Scheme 1) involve the addition of organometallic reagents to aromatic aldehydes (Narita et al 2011;Abou Nakad et al 2018). Nevertheless, the above procedures suffer from several limitations, such as anhydrous conditions, high or very low temperatures as well as the use of harmful reagents.…”
Section: Introductionmentioning
confidence: 99%